Seasonal Variation of Irrigation Water Quality in Bachok, Kelantan - Mohamed Hamim, Norlida; Shahrun, Mohammad Shahid; Jaafar, Jamaliah; Abdul Halim, Azhar; Juneng, Liew (International Journal of Integrated Engineering, 2025)
Agriculture is dependent on an adequate supply of suitable irrigation water quality. Physicochemical analysis of surface water for irrigation was conducted in Bachok, Kelantan during wet and dry period from July 2021 to December 2022. Surface water sampling points consist of primary, secondary and tertiary irrigation canals supplying water for paddy plantation.  This study aimed to evaluate water quality trends in irrigation canals based on physicochemical parameters and discuss its pollution level and irrigation suitability using the Water Quality Index (WQI), National Water Quality Standards (NWQS) and irrigation suitability classification. It was observed that water quality was within NWQS Class IV except DO, Ammoniacal Nitrogen and TSS in locations with intensive aquaculture.  ANOVA analysis showed a significant difference between water quality parameters and sampling locations (p